2011
DOI: 10.1007/s11214-011-9777-9
|View full text |Cite
|
Sign up to set email alerts
|

ARTEMIS Science Objectives

Abstract: NASA's two spacecraft ARTEMIS mission will address both heliospheric and planetary research questions, first while in orbit about the Earth with the Moon and subsequently while in orbit about the Moon. Heliospheric topics include the structure of the Earth's magnetotail; reconnection, particle acceleration, and turbulence in the Earth's magnetosphere, at the bow shock, and in the solar wind; and the formation and structure of the D.G. Sibeck ( ) Code 674, GSFC/NASA,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 202 publications
0
33
0
Order By: Relevance
“…In this event study, a burst of midtail BBFs was observed by the two ARTEMIS probes (Sibeck et al, ), P1 and P2, at ~05:25 UT on 6 December 2014 at X ~ −60 R E . ARTEMIS magnetic field vectors (3 s resolution) were measured by the fluxgate magnetometer (FGM) instrument (Auster et al, ), and plasma moments (3 s resolution) were measured by the electrostatic analyzer (ESA, 0.006–20 keV/q for ions and 0.007–26 keV for electrons) (McFadden et al, ) and the solid‐state telescope (SST, 35 keV–6 MeV for ions and 30 keV–6 MeV for electrons).…”
Section: Bbfs and Plasma Bubble In Midtailmentioning
confidence: 72%
“…In this event study, a burst of midtail BBFs was observed by the two ARTEMIS probes (Sibeck et al, ), P1 and P2, at ~05:25 UT on 6 December 2014 at X ~ −60 R E . ARTEMIS magnetic field vectors (3 s resolution) were measured by the fluxgate magnetometer (FGM) instrument (Auster et al, ), and plasma moments (3 s resolution) were measured by the electrostatic analyzer (ESA, 0.006–20 keV/q for ions and 0.007–26 keV for electrons) (McFadden et al, ) and the solid‐state telescope (SST, 35 keV–6 MeV for ions and 30 keV–6 MeV for electrons).…”
Section: Bbfs and Plasma Bubble In Midtailmentioning
confidence: 72%
“…THEMIS and ARTEMIS [ Angelopoulos , 2008, 2011; Sibeck et al , 2011] provide a new opportunity to examine global solar wind entry modes, by making simultaneous subsolar and distant flank observations for the first time. Here we present new observations from ARTEMIS showing the survival of FTE flux ropes far along the tail magnetopause at x = −67 R E on the dusk flank, with flux content similar to that of FTEs at the dayside.…”
Section: Introductionmentioning
confidence: 99%
“…The particle and magnetic field measurements from the two ARTEMIS probes (P1 and P2) [Sibeck et al, 2011] are used. The probes orbit the Moon with distances <~5 R E from the Moon.…”
Section: Datamentioning
confidence: 99%